Pharmacist’s readiness to manage risks of drug-related problems associated with escitalopram therapy (according to survey data) - Chertkova, Oleksandra; Hoshtynar, Kateryna (The Ukrainian Scientific Medical Youth Journal, 2025)
the global consumption of psychotropic medications has been increasing significantly, and in Ukraine, this trend has been especially exacerbated by the full-scale war. Escitalopram, a selective serotonin reuptake inhibitor, is widely used in the treatment of anxiety and depressive disorders. Its use is associated with a risk of drug-related problems, including adverse drug reactions and drug–drug interactions, particularly among vulnerable populations. The objective of this study was to assess the readiness of pharmacists to manage drug-related risks associated with the use of escitalopram. Given the high prescribing rates and the prevalence of adverse reactions—especially under conditions of polypharmacy and comorbidity—ensuring adequate pharmaceutical care during the dispensing of this prescription medication is critical. We conducted a survey using an online questionnaire distributed via the Google Forms platform. The study involved 103 pharmaceutical professionals from various pharmacy institutions across Ukraine, between February and April 2025. The questionnaire collected data on professional experience, knowledge of drug-related adverse effects and interactions, as well as current counseling practices. Most respondents (68%) were pharmacists with 1 to 5 years of experience. According to the results, nearly half of the pharmacists (48.5%) reported that they do not counsel patients at all regarding the risks associated with escitalopram use. Only 6.8% of respondents rated their awareness of potential adverse effects as high, while the majority considered it low or moderate. A considerable proportion (70%) lacked sufficient knowledge of drug interactions related to escitalopram, and approximately one-third were unaware of the risk of QT interval prolongation. Search engines were found to be the primary source of information for pharmacy staff (52.4%), while the use of professional scientific databases, such as PubMed, remains limited (17.5%). At the same time, all respondents indicated a need for further training. The findings of the study emphasize the importance of implementing structured, targeted educational programs for pharmacists that address the current challenges of pharmacotherapy, as well as integrating evidence-based digital tools. Such an approach may contribute to enhancing the awareness and preparedness of pharmacy professionals and strengthening their role in the prevention of drug-related problems associated with psychotropic medications, particularly in the use of escitalopram in patients with comorbid conditions requiring treatment for anxiety and depressive disorders. The article also outlines a pharmacist’s action algorithm when dispensing the medication, including risk assessment, patient counseling, pharmacovigilance, and the application of innovative tools.